Indonesian sharia fintech services and social media usage - Abdillah, Leon; Mukti, Yogi; Puspita, Desi; Suhartini, Suhartini (Bulletin of Social Informatics Theory and Application, 2021)
Mobile and information technology have reconfigured the global towards a digital system including the digital economy and its payment technology through mobile applications and social media. COVID-19 pandemic has triggered all parties to accelerate and expand IT-based and digital services. The limited of studies related to Islamic Fintech in Indonesia is the main reason for writing this article. Continuing the previous research, it is known that Indonesia in general has followed the era with many Fintechs and startups growing. However, there are still very few Sharia-based services. After conducting online surveys with a number of agencies such as OJK, Fintech Islami Indonesia, it is known that 10 out of 121 Fintechs operate or serve sharia schemes. They provide financial services for:  SMEs and MSMEs (60.00%), General or Consumptive Financing (30.00%), and Property (30.00%), followed by Umrah and Hajj (20.00%), Education (10.00%), and Health (10.00%). Most of the Indonesian sharia fintech (60%) already have mobile-based applications, both Android and iOS. The most widely used social media are Instagram and Facebook, in addition to Twitter, LinkedIn, WhatsApp, and YouTube. In the future, it is hoped that more Indonesian Islamic Fintechs include those serving other sectors such as Agriculture, Forestry, Maritime Affairs and Fisheries, linked to crypto-currency, etc.